Penerapan Aplikasi Pelayanan Desa untuk Implementasi Smart Village di Desa Mangunjaya - Mayadi, Mayadi; Priatna, Wowon; Setiawati, Siti (Journal Of Computer Science Contributions (JUCOSCO), 2023)
Desa Mangunjaya , which is located at Jalan Pendidikan 1 No.13 Mangunjaya, South Tambun District, Bekasi, West Java 17510, is still developing information technology. This village in conveying information is still done manually so that the potential of the village is less published, with that the village community still has difficulty receiving information from the village government and conveying various suggestions and aspirations of the community. In conveying information it is still done manually so that the potential of the village is not published. The problem faced by Mangunjaya village is that the community has difficulty in getting information and complaints in conveying aspirations to the village. The making of certificates is still carried out by the community directly to village officials. The goal in this PKM is to implement a smart village to make the village digitized by designing the Village Service application to make it easier to submit letters from villagers. The method in Community Service is to design an application and conduct socialization for the use of the Application to the community, RT, RW and Village Officials. The result of this PKM is that the Village service application to support Smart Village can be used and training has been carried out for using the Application.